Question of Presence and Viability of Architectural Type as a Legal Rule in Croatian Urban Planning - Ante Senjanović (Prostor)
“Type” can serve as a positive legal term in physical planning and a review of the literature clarifies its specific meaning, distinguishing it from its colloquial usage, where it is often confused with “class.” In architectural theory, the meaning of “type” is rooted in concepts of similarity and indeterminacy, which parallels its meaning in legal theory, where it stands in contrast to the identity and determinacy associated with “class.” This distinction establishes a fundamental limitation on the usability of “type” in legal regulation: the challenge of determining the meaning of a “type” in concrete situations, leading to potential legal uncertainty. An analysis of how the class of singlefamily houses is regulated in Croatian urban development plans reveals that “type” is typically used only as a general requirement for the conformity of building appearances with the surrounding built environment. Rather than relying on “type,” the planning rules predominantly focus on objectively determinable quantitative values assigned to specific building classes.